ANALISIS IMPLEMENTASI BUDAYA ORGANISASI ORGANIZATIONAL CULTURE ASSESSMENT INSTRUMENT (OCAI) PADA PT. ASMORO JATI SEJATI BLORA - Suparwi, Suparwi; Ramadhana, Egga Syifani (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2023)
This study aims to determine the application of organizational culture using the Organizational Culture Assessment Instrument (OCAI) method at PT. Asmoro Jati Sejati Blora, OCAI’s organizational culture is able to form employees who have good performance. This research is a type of field research (field research) and a descriptive qualitative research approach. Data collection techniques using the methods of observation, interviews, and documentation. The subject of this research is the Director of PT. Asmoro Jati Sejati, Representative Manager, Production Manager/PPIC (Production Planning and Inventory Control), Personnel (HR Manager), and production employees of PT. Asmoro Jati Sejati Blora. From this research, it can be concluded that the organizational culture at PT. Asmoro Jati Sejati Blora is a well-controlled and structured company with the hope of employees who want a well-controlled and organized company and a comfortable and appropriate work environment in forming employees to have good performance. So that the organizational culture in PT. Asmoro Jati Sejati Blora can be classified as a hierarchical culture. In addition to the hierarchical culture, PT. Asmoro Jati Sejati also takes several elements from a competitive and result-oriented type of market culture